In Standing, Corticospinal Excitability Is Proportional to COP Velocity Whereas M1 Excitability Is Participant-Specific - Nandi, Tulika; Lamoth, Claudine J. C.; van Keeken, Helco G.; Bakker, Lisanne B. M.; Kok, Iris; Salem, George J.; Fisher, Beth E.; Hortobágyi, Tibor (Frontiers in Human Neuroscience, 2018)
Reductions in the base of support (BOS) make standing difficult and require adjustments in the neural control of sway. In healthy young adults, we determined the effects of reductions in mediolateral (ML) BOS on peroneus longus motor evoked potential (MEP), intracortical facilitation (ICF), short interval intracortical inhibition (SICI) and long interval intracortical inhibition (LICI) using transcranial magnetic stimulation. We also examined whether participant-specific neural excitability influences the responses to increasing standing difficulty. Repeated measures ANOVA revealed that with increasing standing difficulty MEP size increased, SICI decreased (both p < 0.05) and ICF trended to decrease (p = 0.07). LICI decreased only in a sub-set of participants, demonstrating atypical facilitation. Spearman’s Rank Correlation showed a relationship of r = 0.50 (p = 0.001) between MEP size and ML COP velocity. Measures of M1 excitability did not correlate with COP velocity. LICI and ICF measured in the control task correlated with changes in LICI and ICF, i.e., the magnitude of response to increasing standing difficulty. Therefore, corticospinal excitability as measured by MEP size contributes to ML sway control while cortical facilitation and inhibition are likely involved in other aspects of sway control while standing. Additionally, neural excitability in standing is determined by an interaction between task difficulty and participant-specific neural excitability.